Ecological wastewater treatment with activated clays and its reuse in asparagus plants - Cuba Cornejo, Carmen Luz (2022)
Water treatment, abundant clay in the area, for the elimination of particles and microorganisms in wastewater and disinfection through alcoholic extract of the molle, which has a high concentration of tannins that acts as a germicide, not affecting the asparagus during cold washing, saving thousands of cubic meters of groundwater daily. The study has explanatory level and experimental design. The weekly sample (drinking water, residual water and treated water) taken during 3 months, equivalent to 36 water samples. The flocculant capacity of the activated clays depends on the pH of the wastewater, tests were carried out to determine the pH, the experimental tests indicated that pH‹7 its flocculant capacity is restricted as with pH› 7, for which it is worked with a pH7, that is to say neutral. It is concluded that the flocculant capacity of the activated clays was 82.92%, ensuring water treatment. The adequate concentration of activated clays is 60 mg/L, achieving a maximum flocculation of 82.92%. Activated clays have action on pathogenic microorganisms: Escherichia coli, fecal coliforms and total coliforms, which are eliminated, since they are dragged by the flocs to the bottom of the container, leaving the supernatant water free.